2003
DOI: 10.1159/000074792
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and Arterial Wall Disease

Abstract: Rapid progress in non-invasive ultrasound techniques has resulted in a wide variety of clinical applications for the assessment of cerebrovascular diseases. Recent highlights in ultrasound research include the evaluation of vascular ageing as a degenerative process, the demonstration of plaque development, motion and vulnerability in atherosclerosis and multi-dimensional as well as innovative imaging techniques (e.g., compound imaging) to depict early and small vascular lesions. In addition, echo-contrast agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 92 publications
1
29
0
3
Order By: Relevance
“…Whether differences in plaque echogenicity or surface morphology can predict the clinical expression of atheroma is still debated. 11 Recent studies have shown that high-resolution MRI can visualize FCT and rupture in vivo. 10 However, the availability of this technique is currently very limited, and the data obtained are qualitative and not quantitative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether differences in plaque echogenicity or surface morphology can predict the clinical expression of atheroma is still debated. 11 Recent studies have shown that high-resolution MRI can visualize FCT and rupture in vivo. 10 However, the availability of this technique is currently very limited, and the data obtained are qualitative and not quantitative.…”
Section: Discussionmentioning
confidence: 99%
“…11 The FC covered an area of weaker echoes that corresponded to lipid accumulation (lipid core). We have developed a system that finds the 2 paths within a specified area that best follow the hypoechogenic-hyperechogenic and hyperechogenichypoechogenic boundaries and then measures the distance between them ( Figure 2C).…”
Section: Ultrasound System For the Measurement Of Fctmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the overall accuracy of using B-mode sonography against criterion standard techniques (DSA or histopathology) is not high (sensitivity and specificity ranges from 39% to 89% and 72% to 87%, respectively). [27][28][29] Several studies have noted that its accuracy decreases with the increasing degree of stenosis, 30,31 and it has even failed to detect ulceration in high-grade stenosis. 29 The application of color-flow Doppler-assisted duplex imaging, which combines the B-mode and blood-flow velocity information, 32 also shows limitations in providing adequate information to identify plaque ulcerations.…”
Section: Sonographymentioning
confidence: 99%
“…Although many studies have validated the measurement of IMT, it is clear that many distinct biological pathways and mechanisms may be reflected by the measurement. For example, IMT may represent hypertensive medial hypertrophy [96,97], compensatory intimal thickening owing to mechanical forces of blood flow [98,99] or the initial 'fatty streak' stage of atherosclerosis that involves accumulation of macrophage foam cells in the artery wall [100].…”
Section: Motivationmentioning
confidence: 99%